Modeling solar energetic particle events using ENLIL heliosphere simulations. Issue 7 (28th July 2017) - Luhmann, J. G.; Mays, M. L.; Odstrcil, D.; Li, Yan; Bain, H.; Lee, C. O.; Galvin, A. B.; Mewaldt, R. A.; Cohen, C. M. S.; Leske, R. A.; Larson, D.; Futaana, Y.
Abstract: Solar energetic particle (SEP) event modeling has gained renewed attention in part because of the availability of a decade of multipoint measurements from STEREO and L1 spacecraft at 1 AU. These observations are coupled with improving simulations of the geometry and strength of heliospheric shocks obtained by using coronagraph images to send erupted material into realistic solar wind backgrounds. The STEREO and ACE measurements in particular have highlighted the sometimes surprisingly widespread nature of SEP events. It is thus an opportune time for testing SEP models, which typically focus on protons ~1–100 MeV, toward both physical insight to these observations and potentially useful space radiation environment forecasting tools. Some approaches emphasize the concept of particle acceleration and propagation from close to the Sun, while others emphasize the local field line connection to a traveling, evolving shock source. Among the latter is the previously introduced SEPMOD treatment, based on the widely accessible and well‐exercised WSA‐ENLIL‐cone model. SEPMOD produces SEP proton time profiles at any location within the ENLIL domain. Here we demonstrate a SEPMOD version that accommodates multiple, concurrent shock sources occurring over periods of several weeks. The results illustrate the importance of considering longer‐duration time periods and multiple CME contributions in analyzing, modeling, and forecasting SEP events. Key Points: Solar energetic particle event models with potential for forecasts are needed SEPMOD is a model that represents an option, using routinely run ENLIL simulation results The model can be applied to any observer location within the ENLIL simulation domain, including planetary sites